PENGARUH PAPARAN MEDIA DIGITAL TERHADAP PERKEMBANGAN BAHASA AGRESIF PADA ANAK USIA 3-6 TAHUN - Allyana; Depalina, Syamsiah (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
The rapid advancement of digital technology has significantly altered the interaction patterns and activities of Early Childhood. Children aged 3-6 years are now increasingly exposed to various forms of digital media, including content that potentially contains aggressive elements. This journal aims to analyze the influence of digital media exposure on the development of aggressive language in children aged 3-6 years.Through a literature review and psychosocial impact analysis, it was found that excessive exposure to aggressive digital media content—such as harsh words, threats, or verbal intimidation can lead to aggressive language use in children's social interactions. Therefore, this journal emphasizes the importance of strict parental supervision, early media literacy, and the creation of a positive communication environment for children to use digital media appropriately.